Rice proteins – Gum arabic coacervates: Effect of pH and polysaccharide concentration in oil-in-water emulsion stability - Igartúa, Daniela (2024)
In the context of replacing animal proteins in food matrices, rice proteins (RP) become promised because they come from an abundant plant source, are hypoallergenic, and have high digestibility and nutritional value. However, commercial protein isolates obtained by spray drying have low solubility and poor functionality, especially in their isoelectric point. One way to modify these properties is through interaction with polysaccharides, such as gum arabic (GA). Therefore, this work aims to evaluate the effects of pH and GA concentration on the interaction and emulsifying activity of RP:GA coacervates. First, the effects of pH (2.5 to 7.0) and GA concentrations (0.2 to 1.0 wt%, giving rise to RP:GA mass ratios of 1:0.2 to 1:1.0) in RP:GA blends were evaluated. The results demonstrated that biopolymers present opposite net charges at pH between 2.5 and 4.0. At pH 3.0, insoluble coacervates with complete charge neutralization were formed by electrostatic interactions, while at pH 5.0 it was observed that the presence of GA prevented the RP massive aggregation. Second, selected blends with 0.4 or 1.0 wt% of GA (RP:GA mass ratios of 1:0.4 or 1:1.0) at pH 3.0 or 5.0 were tested for their ability to stabilize oil-in-water emulsions. The emulsions were characterized for 21 days. It was observed that the GA increased the stability of RP emulsions, regardless of the pH and polysaccharide concentration. Taken together, our results show that it is possible to combine RP and GA to improve the emulsifying properties of these plant proteins at pH conditions close to their isoelectric point, expanding the possibility of implementation in food systems